Cranial Nerve Palsies: Sarcoidosis to Systemic Lupus Erythematosus - Fawad Aslam; Firas Bannout; Elizabeth B. Russell (Case Reports in Rheumatology)
Cranial palsies are a very rare feature of SLE. Similarly, peripheral sensory-motor axonal neuropathy is very uncommon in SLE. The combination of the two as the presenting symptoms of SLE is a diagnostic challenge particularly in an elderly male patient with a known diagnosis of sarcoidosis. This case serves to highlight the diagnostic considerations in such a patient. The lack of response to standard therapy and the presence of subtle clues like anemia, proteinuria, and mild serositis should prompt the physician to look for alternate diagnoses. The potential association of SLE and sarcoidosis is also discussed. SLE can be present in elderly male patients with cranial and peripheral neuropathy.